2005
DOI: 10.1300/j229v06n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Hebrew-Multidimensional Inventory of Dissociation (H-MID): A Valid and Reliable Measure of Pathological Dissociation

Abstract: ABSTRACT. The Multidimensional Inventory of Dissociation (MID;Dell, 2004b) has 168 dissociation items and 50 validity items. The MID assesses 14 major facets of dissociation, 23 symptoms of dissociation, and has 5 validity scales. The MID operationalizes (a) the subjective/ phenomenological domain of dissociation, and (b) 23 hypothesized symptoms of dissociative identity disorder (DID). This article describes the development of a Hebrew version of the MID (H-MID). In a sample of clinical and nonclinical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
1
12
1
1
Order By: Relevance
“…The differences are stark. In the mixed samples (Dell, 2006a;Somer & Dell, 2005), mean MID scores were significantly correlated with TEQ scores (rs = .38 to .70; median r = .56), whereas this was not the case with our sample of schizophrenia patients (rs = -.22 to .08; median r = -.02). This result raises a question: Is this finding a Type II error, or does the MID measure something different in schizophrenia patients than it does in DID?…”
Section: The Relation Between Mid Scores and Childhood Maltreatment Scontrasting
confidence: 87%
See 1 more Smart Citation
“…The differences are stark. In the mixed samples (Dell, 2006a;Somer & Dell, 2005), mean MID scores were significantly correlated with TEQ scores (rs = .38 to .70; median r = .56), whereas this was not the case with our sample of schizophrenia patients (rs = -.22 to .08; median r = -.02). This result raises a question: Is this finding a Type II error, or does the MID measure something different in schizophrenia patients than it does in DID?…”
Section: The Relation Between Mid Scores and Childhood Maltreatment Scontrasting
confidence: 87%
“…Because the TEQ was not administered to the DID patients, we compared the MID and TEQ data from the schizophrenia patients with the MID and TEQ data from two previous studies of mixed samples of clinical and nonclinical participants (Dell, 2006a;Somer & Dell, 2005; see Table 5). The differences are stark.…”
Section: The Relation Between Mid Scores and Childhood Maltreatment Smentioning
confidence: 99%
“…The MID was translated into Hebrew and the translated version was used with the Israeli sample. Previous analyses of the psychometric properties of the Hebrew version of the MID (Somer & Dell, 2005) yielded promising findings. The H-MID total score and the 13 primary scales were significantly correlated with the DES (r = .53-.70) and with the total number of traumas endorsed.…”
Section: Multidimensional Inventory Of Dissociation (Mid 4(p)mentioning
confidence: 99%
“…It is recommended that further research is undertaken in this area with a view to developing our understanding regarding this relationship. Somer & Dell, 2005)) 3. Multiple regression analysis showed that the significant predictor of dissociation in the Schizophrenia group was voices and in the DID group was ego-alien experiences amnesia, absorption and depersonalisation scores) and AH's and intensity (multiple) of trauma.…”
mentioning
confidence: 99%